Logistics management of Pantai Timor Hypermarket Sdn Bhd - Abdul Rasyid, Mira; Kua Geok Chin, Eileen; Mohd Noor, Ili Aidid (2015)
This research is to examine the logistic management in Pantai Timor Hypermarket. A survey was created containing case study of Pantai Timor Hypermarket Sdn Bhd in Pengkalan Chepa. Interview was used in collecting data for this research. The research begins by introducing the research area and moves on to discuss the terms direct related to the logistics management and the result of the term based on logistic management. The areas are consist of inventory management, information technology system, transportation management and warehouse management. Lastly, the research recommends some of way to improve the logistic management of Pantai Timor Hypermarket in the future